PENGARUH EDUKASI TERHADAP TINGKAT PENGETAHUAN TENTANG PERAWATAN DIRI PENGGUNAAN AKSES ARTERIOVENOUS SHUNT (AV SHUNT) PASIEN HEMODIALISA - Zaky Mubarak (NHM PRESS, 2022)
Kidney failure is a disorder of kidney function or damage to the kidney that has lasted for 3 months or more. Providing health education is one thing that needs to be considered in the management of patients with chronic kidney disease undergoing hemodialysis. The aim of this study is to determine the effect of education on the level of self-care knowledge of patients with AV Shunt – access. This study used a quantitative design with a quasi-experimental method with control group. The results of this study is the group that was given the education treatment had a p value of 0.000, while the control group had a p value of 0.302. Education improve the knowledge level of arteriovenous shunt (AV Shunt) access self-care on hemodialysis patients.